Alkali-activated all-solid waste cementing mortar material and preparation method thereof

By activate aluminum mud at low temperature and combining it with other materials, alkali-activated all solid waste gelling mortar material is prepared, which solves the problem of solid waste treatment of aluminum foil anode mud, and achieves efficient utilization of resources and improvement of performance.

CN119504194APending Publication Date: 2025-02-25HUBEI POLYTECHNIC UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411674746.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing technology lacks effective resource-based treatment methods to utilize aluminum foil anode sludge solid waste, resulting in its stacking and strong alkalinity, causing environmental pollution and resource waste.

Method used

Aluminum mud is treated by low-temperature thermal activation and combined with alkaline exciters, mineral powder, fly ash and river sand and other materials to prepare an alkali-excited all-solid waste gelling mortar material. The material forms a gelled structure with high strength and durability through alkali excitation reaction.

Benefits of technology

It realizes the reuse of aluminum mud solid waste, improves resource recycling rate, is simple in preparation process, saves costs, and meets the requirements of building materials in terms of mechanics, stability, corrosion resistance, high temperature resistance and other properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504194A_ABST
    Figure CN119504194A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste resource utilization, in particular to an alkali-activated all-solid waste cementing mortar material and a preparation method thereof.The alkali-activated all-solid waste cementing mortar material is prepared from, by weight, 10-40 parts of aluminum mud subjected to low-temperature thermal activation, 3-5 parts of an alkali activator, 20-45 parts of mineral powder, 30-60 parts of silica fume or fly ash, river sand and water; the alkaline activator comprises water glass and sodium hydroxide; the alkali-activated all-solid waste cementing mortar is a novel inorganic material which is green, pollution-free and durable, the pretreatment of solid waste is simple, the preparation method of the cementing material is simple, the strength can be rapidly improved only through reasonable maintenance, and the construction cost is reduced. In other aspects, such as mechanical properties, stability, corrosion resistance and high temperature resistance, the requirements of building materials can be met, and the market prospect is relatively great.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste resource utilization, and in particular to an alkali-activated all-solid waste gelling mortar material and a preparation method thereof. Background Art

[0002] The rapidly developing modern industry has higher and higher requirements for the performance and quantity of aluminum electrolytic capacitors, among which anode foil is the key to restricting medium-voltage and high-capacity aluminum electrolytic capacitors. In the process of preparing anode foil, Al2O3 and fluoridating agent are added to the aluminum electrolytic cell, and electrolyte liquid is formed after heating. In the electrolyte, Al2O3 is generated on the surface of aluminum foil by anodic oxidation, but during the preparation process, Al2O3 will combine with fluoride in the electrolyte, and the generated aluminum hydrogen oxalate will dissolve in the electrolyte and gradually precipitate on the anode surface to form anode mud. At present, the disposal method of anode mud is to obtain aluminum-containing solid waste (abbreviated as aluminum mud) through preliminary neutralization with quicklime. The main components are CaCO3, Al(OH)3 and a small amount of solid impurities. It is an alkaline and insoluble industrial residue. The effective utilization and treatment of aluminum mud is a major problem in solid waste treatment. Large-scale stacking and strong alkalinity will cause environmental pollution and waste of resources. There is currently no effective resource treatment method.

[0003] Geopolymer is a new type of polymer material obtained by chemical reaction at a low temperature under alkali excitation with active Al2O3 and SiO2 as raw materials. Compared with traditional cement, it has high early strength, good stability, chemical corrosion resistance, good impermeability, high temperature resistance and other performances. At the same time, it has the advantages of abundant sources, low price, simple process and resource saving. As a new inorganic polymer material, geopolymer can be sourced from minerals containing silicon and aluminum (high-grade soil) and industrial solid waste (red mud, tailings, steel slag, fly ash, etc.). At a low temperature, it reacts with alkali excitation, first breaking the bond and then repolymerizing to form chemical bonds mainly composed of ions and covalent bonds. Silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron work together to alternately polymerize an oxygen atom to form a gelling material with a structure like a three-dimensional network structure. Due to its unique structure, it has great advantages in thermodynamics, salt-alkali resistance and corrosion resistance. However, there is currently a lack of solutions to apply aluminum foil anode mud solid waste to geopolymers. Therefore, it is urgently needed to be solved.

[0004] The above contents are only used to assist in understanding the technical solution of the present invention, and do not constitute an admission that the above contents are the closest prior art. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an alkali-activated all-solid waste gelled mortar material and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the technical scheme of the present invention is implemented as follows: an alkali-activated all-solid waste cementitious mortar material and a preparation method thereof, measured by weight, comprising: 10-40 parts of aluminum mud after low-temperature thermal activation, 3-5 parts of alkaline activator, 20-45 parts of mineral powder, 30-60 parts of silica ash or fly ash, river sand, and water; the alkaline activator comprises water glass and sodium hydroxide.

[0007] Preferably, the water-to-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 0.3-0.45, the sand-to-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 3:1-4:1; the ratio of mineral powder to fly ash in the alkali-activated all-solid waste cementitious mortar material is 3:7-5:5.

[0008] Preferably, the alkaline excitation modulus of the alkaline activator is 1.0-1.6.

[0009] Preferably, the alkaline activation modulus of the alkaline activator is 1.2; the modulus of the water glass is 3.0, and the water content of the water glass is 26.2%; and the purity of the sodium hydroxide is 98.0%.

[0010] Preferably, the mineral powder includes Al2O3 and SiO2 amorphous structures, and the particle size of the mineral powder is 10 μm; the fly ash includes Al2O3, SiO2, and CaO amorphous structures; and the silicon powder includes SiO2 amorphous structures.

[0011] Preferably, the preparation method comprises the following steps:

[0012] (a) placing the wet aluminum mud solid waste in an electric constant temperature blast drying oven at 180° C. for 3 hours, taking it out after cooling it to room temperature, and then crushing and grinding it in a ball mill, sieving it through a 600-mesh screen to obtain low-temperature heat-activated aluminum mud, and sealing the low-temperature heat-activated aluminum mud in a packaging bag for subsequent use;

[0013] (b) preparing an alkaline activator by mixing sodium hydroxide and water glass;

[0014] (c) First, prepare the raw materials in proportion, put the mineral powder, fly ash and the aluminum mud activated by low temperature heat in step (a) into a mortar mixing equipment, then add the alkaline activator solution and water prepared in step (b), pour the weighed river sand into the funnel of the mortar mixing equipment, and then start the mixing equipment to stir to obtain a slurry.

[0015] (d) The slurry obtained in step (c) is fed into a mold, and the mold containing the slurry is placed in a vibration device for at least 60 seconds to vibrate the slurry in the mold.

[0016] (e) The mold containing the compacted slurry in step (d) is placed at room temperature for curing for 24 hours and then demolded, and the block slurry after demolding is placed indoors for curing for 28 days to obtain an alkali-activated all-solid waste cementitious mortar.

[0017] Preferably, in step (a), Al(OH)3 in the low temperature thermally activated aluminum mud is decomposed into γ-Al2O3; the γ-Al2O3 constitutes the Al source for preparing AlO-Si geopolymer.

[0018] Preferably, when the mass fraction of the low-temperature heat-activated aluminum mud in step (c) is 0-40%, the flexural strength of the alkali-activated all-solid waste cementitious mortar material obtained in step (e) is 2.1MP-7.9MP; the compressive strength of the alkali-activated all-solid waste cementitious mortar material is 4.63MPa-67.63MPa.

[0019] Preferably, when the mass fraction of the low-temperature thermally activated aluminum mud in step (c) is 10%, the maximum flexural strength of the alkali-activated all-solid waste cementitious mortar material obtained in step (e) is 7.9MPa; the maximum compressive strength of the alkali-activated all-solid waste cementitious mortar material is 67.63MPa.

[0020] Preferably, the process of preparing the alkaline activator in step (b) comprises:

[0021] b1. Prepare water glass (sodium silicate) and sodium hydroxide in proportion according to the modulus requirements of the alkaline activator;

[0022] b2. Add water glass and sodium hydroxide gradually into a container according to a certain ratio and stir evenly;

[0023] b3. Add water to adjust the concentration of the alkali activator according to actual needs;

[0024] b4. Continue stirring the mixture to ensure uniformity of the base activator;

[0025] b5. Store the prepared alkaline activator in a sealed container for future use.

[0026] The beneficial effects of the present invention are embodied in:

[0027] The alkali-activated all-solid waste gelling mortar provided by the present invention is a green, pollution-free, durable new inorganic material, which realizes the reuse of aluminum mud solid waste and improves the resource recycling rate. In addition, the low-temperature thermal activation temperature for aluminum mud solid waste is only 180°C, and no high-temperature calcination is required, which saves costs. At the same time, the material preparation method is simple, and only reasonable maintenance is required to rapidly improve its strength, so that it can meet the requirements of building materials in terms of mechanics, stability, corrosion resistance, high temperature resistance and other properties, and has a large market prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is the experimental process flow chart of the present invention;

[0029] Figure 2 is the TG-DSC curve of the aluminum mud of the present invention;

[0030] Figure 3 This is the Raman graph of the test block cured for 3 days under the conditions of aluminum mud-silicon fume with and without NaOH after treatment of the present invention;

[0031] Figure 4 This is a comparison chart of the flexural strength of the geopolymer containing treated aluminum mud-mineral powder-fly ash after curing for 28 days;

[0032] Figure 5 Table 2-3 of the present invention contains a comparison chart of the compressive strength of aluminum mud-slag-fly ash mortar test blocks treated with different mass fractions after 28 days of curing;

[0033] Figure 6 This is the XRD spectrum of the mortar test block containing 10% by mass of aluminum mud powder-fly ash after curing for 28 days. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the comparative examples. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0035] Example 1

[0036] An alkali-activated all-solid waste gelled mortar material and a preparation method thereof, comprising: aluminum mud after low-temperature thermal activation treatment, an alkaline activator, water, mineral powder, fly ash, and river sand with uniform particle size. The alkaline activator includes water glass and sodium hydroxide. The water glass is an industrial-grade liquid sodium silicate produced and sold on the market, which is a yellow-green viscous liquid; the modulus of the water glass is 3.0, and the water content of the water glass is 26.2%. In the untreated aluminum mud solid waste, CaCO3 accounts for 16%, and Al(OH)3 accounts for the highest content of 72.1%.

[0037] The water-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 0.3-0.45. The sand-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 3:1-4:1; the ratio of mineral powder to fly ash in the alkali-activated all-solid waste cementitious mortar material is 3:7-5:5. The alkali activation modulus of the alkaline activator is 1.0-1.6.

[0038] In the specific operation, the water-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 0.4. The sand-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 3:1. The ratio of mineral powder to fly ash in the alkali-activated all-solid waste cementitious mortar material is 3:7. The alkali activation modulus of the alkaline activator is controlled at 1.2. The sodium hydroxide is a white translucent granular crystal particle, and the purity of the sodium hydroxide is 98.0%.

[0039] Analysis of the composition of aluminum foil anode mud

[0040] The element content (wt.%) of aluminum foil anode mud (abbreviated as aluminum mud) was obtained after EDS testing and is shown in Table 2-1. As shown in Table 2-1, in this industrial waste, the metal elements Al and Ca account for about 27.8% and 4.6% respectively, as well as trace amounts of Na (0.9%) and Mg (1.0%), with the highest content of metal Al; non-metallic elements include O, P, and Cl, with mass proportions of 54%, 5.7%, and 6.1% respectively, with O having the highest content.

[0041] Table 2-1 Element Content of Aluminum Foil Anode Mud

[0042]

[0043] The composition and content of aluminum mud obtained by chemical precipitation method are shown in Table 2-2. The statistical results in Table 2-2 show that the original solid waste is mainly composed of CaCO3, Al(OH)3 and a small amount of solid impurities (polyacrylamide complexed metal compounds insoluble in acid such as calcium sulfate and some mud) and soluble salts (including sodium chloride, phosphate, nitrate, ammonium salt, etc.). Among them, CaCO3 accounts for 16%, and Al(OH)3 accounts for the highest content of 72.1%.

[0044] Table 2-2 Composition of aluminum foil anode mud

[0045]

[0046] Based on the analysis results of Table 2-1 and Table 2-2, it can be seen that the main metal element contained in aluminum mud solid waste is Al, which exists in the form of hydroxide. Therefore, after the application reasonably treats this component of aluminum mud, it can realize the recycling and reuse of aluminum mud, promote the reuse of solid waste materials, protect the natural environment, and increase economic benefits.

[0047] Example 2

[0048] The preparation method of the alkali-activated all-solid waste gelled mortar material of the present application comprises the following steps:

[0049] (a) The wet aluminum mud is placed in an electric constant temperature air drying oven at 180°C for 3 hours, and then taken out after the aluminum mud is cooled to room temperature, and then crushed and ground in a ball mill, sieved with a 600-mesh screen, and sealed in a packaging bag for subsequent use;

[0050] (b) preparing an alkaline activator;

[0051] (c) First, the weighed mineral powder and fly ash and low-temperature thermally activated aluminum mud are placed into a mortar mixing device, and then the alkaline activator solution prepared in step (b) is added, and the weighed river sand is poured into the funnel of the mortar mixing device and the mixing device is started to stir to obtain a slurry.

[0052] (d) feeding the slurry obtained in step (c) into a mold, and placing the mold containing the slurry in a vibration device for at least 60 seconds to vibrate the slurry in the mold.

[0053] (e) The mold containing the compacted slurry in step (d) is placed at room temperature for curing for 24 hours and then demolded, and the block slurry after demolding is placed indoors for curing for 28 days to obtain an alkali-activated all-solid waste cementitious mortar.

[0054] The present application prepares an alkali-activated all-solid waste cementitious mortar that can replace traditional ordinary silicate cementitious materials by changing the modulus of the alkali activator and the ratio of raw materials, and determines the optimal raw material ratio and alkali-activated modulus for obtaining the alkali-activated all-solid waste cementitious mortar material provided in the present application through compression, flexural tests and microscopic analysis.

[0055] The main experiments are as follows:

[0056] (1) The experiment mainly uses mineral powder, fly ash, aluminum mud solid waste and water as the main raw materials, and uses sodium hydroxide and water glass to prepare alkaline activators to obtain mortar specimens containing different mass fractions of treated aluminum mud (0%-40%). The modulus of water glass used in this experiment is 3.0. The modulus is adjusted to a fixed value of 1.2 by mixing the composite alkaline activator with sodium hydroxide. The prepared mortar specimens are cured for 28 days and their compressive and flexural properties are tested respectively. The 28-day test blocks are analyzed by XRD and other tests, and finally the most suitable ratio is obtained.

[0057] (2) In this embodiment, the mass ratio of mineral powder to fly ash is fixed (3:7) and the modulus is fixed at 1.2 to study the flexural and compressive properties of the mineral powder-fly ash-treated aluminum mud mortar specimens based on alkali-activated properties.

[0058] Designed raw material ratio:

[0059] The mineral powder and fly ash were mixed in a ratio of 3:7, the activator modulus was fixed at 1.2, and treated aluminum mud was added with a mass fraction of 0%-40% respectively. Five groups of experiments were designed as shown in Table 2-3.

[0060] Table 2-3 Design of the mix ratio of aluminum mud-ore powder-fly ash system after treatment

[0061]

[0062] According to the TG-DSC curve of aluminum foil anode mud, aluminum foil anode mud (aluminum mud) is pretreated:

[0063] TG-DSC curve of aluminum foil anode mud:

[0064] Figure 2 It is the TG-DSC curve of aluminum mud in the range of 0-1000℃. Figure 2 The decreasing TG curve in (a) shows that the aluminum mud has a continuous weight loss process under the condition of increasing temperature, and there are relatively obvious endothermic peaks at 150℃, 260℃ and 730℃. The DSC is further processed by derivative and plotted, and there are many relatively significant endothermic peaks. Among them, characteristic peak 1 is the volatilization of free water by heat; characteristic peak 2 is the characteristic peak formed by the dehydration of Al(OH)3 at a low temperature environment of 140-150℃, at which time γ-Al2O3 can be formed, and the oxygen ions in its crystal structure are approximately face-centered close-packed, and Al 3+ It is irregularly distributed in the octahedral and tetrahedral voids surrounded by oxygen ions. Its specific surface area is relatively large and it is a highly active oxide. Characteristic peak 3 is mainly the decomposition of organic matter; 600℃ is mainly the decomposition of AlOOH; characteristic peak 4 is the decomposition of calcium carbonate in aluminum mud.

[0065] Generally, geopolymer raw materials (such as kaolin) need high-temperature calcination, which consumes relatively high energy. In the present invention, highly active γ-Al2O3 can be obtained at a relatively low temperature. Therefore, based on the calcined product and production cost, this application is based on the fact that Al(OH)3 can be decomposed into γ-Al2O3 at a relatively low temperature, and this is used as an Al source for the preparation of Al-O-Si geopolymers. Before preparing the geopolymer, the aluminum mud is pretreated with low-temperature thermal activation. Combined with the above experimental analysis, this application adopts a constant temperature of 180°C for 3 hours to remove free water and promote the decomposition of Al(OH)3, and then crushed, ground and sieved at room temperature to obtain the aluminum mud required for the experiment for the research and development of geopolymer gelling materials.

[0066] Alkaline activator configuration:

[0067] The stimulator used in this experiment is a mixture of sodium hydroxide and water glass.

[0068] ①Prepare materials: water glass (sodium silicate) and sodium hydroxide.

[0069] ② Determine the ratio: Determine the ratio of water glass and sodium hydroxide according to the desired alkali excitation effect. Generally speaking, the amount of sodium hydroxide used is relatively small.

[0070] ③Mixing: Gradually add water glass and sodium hydroxide into a container in a determined proportion and stir evenly.

[0071] ④ Adjust the concentration: According to actual needs, the concentration of the alkali activator can be adjusted by adding an appropriate amount of water.

[0072] ⑤Stirring: Continue to stir the mixture to ensure the uniformity of the alkali activator.

[0073] ⑥Storage: Store the prepared alkaline activator in a sealed container to avoid moisture and contact with other substances.

[0074] Preparation of test blocks:

[0075] First, put the weighed mineral powder and fly ash, and the treated aluminum mud into the mortar mixing pot, then add the prepared alkaline activator solution, rinse the cup wall with a small amount of water, pour the rinsed solution into the mixing pot, and place it on the mixing table. Pour 1350g of standard sand into the funnel and start the switch at the same time. After the mixing is completed, use a scraper to scrape the slurry on the stirring plate, put the slurry in the mixing drum into the triple mold, place it on the vibration table, vibrate for 60s, then take it out and fill the mold again. Repeat the above process and vibrate for 60s.

[0076] The finished triple mold is placed at room temperature for curing for 24 hours and then demolded. It is placed indoors for curing for 28 days and then subjected to flexural and compressive tests.

[0077] Flexural and compressive strength test:

[0078] Use a towel to wipe the specimen clean after 28 days of curing, and then place the relatively flat specimen on the testing machine for flexural test. Place the broken specimen on the testing machine for compression test. The program will automatically record the maximum load of the test block and finally obtain the effective strength.

[0079] like Figure 4 As shown, for the test block without adding aluminum mud, the measured flexural strength is 6.1MPa; for the test block with 10% treated aluminum mud added, the flexural strength increases to 7.9MPa, and the strength is increased by 30%; the flexural strength decreases with the increase of the content of aluminum mud added after treatment, and when the addition amount is 20%, 30% and 40% respectively, the value decreases to 5.7MPa, 4.8MPa and 2.1MPa.

[0080] like Figure 5As shown in the figure, for the mineral powder-fly ash test block without aluminum mud, the measured compressive strength is 38.4MPa. The compressive strength of the mortar test block with 10% treated aluminum mud added will rise to 67.63MPa, and the strength will increase by 76%. The strength will decrease with the increase of the amount of treated aluminum mud added, but when the added mass fraction is 20%, the strength value can still reach 50.82MPa. When the addition amount is 30% and 40% respectively, the compressive strength drops to 33.2MPa and 4.63MPa respectively.

[0081] like Figure 6 As shown in the figure, a relatively obvious quartz peak appears in the sample, which comes from the river sand component in the mortar. In addition, a relatively significant mullite peak appears in the spectrum. New characteristic diffraction peaks appear at 28° and 34°, corresponding to the hydration product CSH and calcium aluminosilicate, respectively, which is the reason why the geopolymer has high strength.

[0082] Compared with the test blocks without aluminum mud, the compressive and flexural strengths of the test blocks after adding 10% aluminum mud were 67.63MPa and 7.9MPa, respectively, and the strength was increased by 76% and 30%, respectively. The improvement in strength is not only due to the formation of a high volume fraction of hydration products with a gelling effect.

[0083] In addition, the components in the treated aluminum mud that do not participate in the hydration reaction can play a micro-aggregate filling effect, fill the tiny pores in the mortar, reduce the porosity, and increase the density. At the same time, the micro-aggregate can disperse the active component slurry in the geopolymer, increase the surface area of ​​Si-O-Al, improve the filling and viscosity of the hydration product, thereby improving fluidity and plasticity, thereby improving the compressive and flexural strength. However, due to the excessive amount of inert filling (40%), the network structure of the geopolymer cementitious material is destroyed and the strength is significantly reduced.

[0084] Raman spectroscopy

[0085] Raman spectroscopy was used to characterize the blocks of alkali-activated all-solid waste cementitious mortar materials after three days of curing to determine the types of chemical bonds and crystal structure changes of the materials. Figure 4 As shown, for 712cm -1 and 270cm -1 The weaker peaks correspond to CO3 2- The stretching vibration and Ca 2+ The most significant peak is located at 1086cm -1 and 1070cm -1 , corresponding to the two main vibration modes of calcium carbonate: tension and bending. 310cm -1 The peak position comes from the stretching vibration mode of the AlO4 unit in γ-Al2O3. For the sample with added NaOH, Figure 4There are no significant characteristic peaks in (b), and a chemical reaction has occurred. This is due to the formation of hydration products with long chains, which leads to increased crystal disorder and difficult vibration of chemical bonds. Raman spectroscopy shows that geopolymers containing alkaline activators (NaOH) form polymers with long chains.

[0086] Through the above experimental data analysis, it can be concluded that the activity of raw materials can be greatly improved in an alkaline environment, the strength of the polymer can be enhanced, and the early strength can be enhanced through natural curing at room temperature. The following conclusions are drawn through the preparation and performance research of aluminum mud geopolymer:

[0087] (1) The different amounts of treated aluminum mud solid waste have a significant effect on the flexural and compressive strength of geopolymer gel. The compressive strength increases with the curing age. When 10% aluminum mud is added, the flexural and compressive strengths can reach 7.9MPa and 67.63MPa. The 28d flexural and compressive strengths of the sample containing 30% treated aluminum mud solid waste are 4.8MPa and 33.2MPa, respectively.

[0088] (2) Under the stimulation of alkaline coagulant, the internal structure of mineral powder and fly ash undergoes depolymerization-condensation reaction, and the generated NASH gel fills the pores, making the sample structure denser and promoting the mechanical properties of the mortar specimen.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An alkali-activated all-solid waste gelled mortar material, characterized in that: The method comprises, by weight, 10-40 parts of aluminum mud after low-temperature thermal activation, 3-5 parts of alkaline activator, 20-45 parts of mineral powder, 30-60 parts of silica ash or fly ash, river sand and water; the alkaline activator comprises water glass and sodium hydroxide.

2. The alkali-activated all-solid waste gelled mortar material according to claim 1, characterized in that: The water-to-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 0.3-0.45, the sand-to-cement ratio of the alkali-activated all-solid waste cementitious mortar material is 3:1-4:1; the ratio of mineral powder to fly ash in the alkali-activated all-solid waste cementitious mortar material is 3:7-5:

5.

3. The alkali-activated all-solid waste gelled mortar material according to claim 2, characterized in that: The alkaline excitation modulus of the alkaline activator is 1.0-1.

6.

4. The alkali-activated all-solid waste gelled mortar material according to claim 3, characterized in that: The alkaline excitation modulus of the alkaline activator is 1.2; the modulus of the water glass is 3.0, and the water content of the water glass is 26.2%; the purity of the sodium hydroxide is 98.0%.

5. The alkali-activated all-solid waste gelled mortar material according to claim 4, characterized in that: The mineral powder includes Al2O3 and SiO2 amorphous structures, and the particle size of the mineral powder is 10 μm; the fly ash includes Al2O3, SiO2, and CaO amorphous structures; and the silicon powder includes SiO2 amorphous structures.

6. The method for preparing an alkali-activated all-solid waste gelled mortar material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (a) placing the wet aluminum mud solid waste in an electric constant temperature blast drying oven at 180° C. for 3 hours, taking it out after cooling it to room temperature, and then crushing and grinding it in a ball mill, sieving it through a 600-mesh screen to obtain low-temperature heat-activated aluminum mud, and sealing the low-temperature heat-activated aluminum mud in a packaging bag for subsequent use; (b) preparing an alkaline activator by mixing sodium hydroxide and water glass; (c) First, prepare the raw materials in proportion, put the mineral powder, fly ash and the aluminum mud activated by low temperature heat in step (a) into a mortar mixing equipment, then add the alkaline activator solution and water prepared in step (b), pour the weighed river sand into the funnel of the mortar mixing equipment, and then start the mixing equipment to stir to obtain a slurry. (d) The slurry obtained in step (c) is fed into a mold, and the mold containing the slurry is placed in a vibration device for at least 60 seconds to vibrate the slurry in the mold. (e) The mold containing the compacted slurry in step (d) is placed at room temperature for curing for 24 hours and then demolded, and the block slurry after demolding is placed indoors for curing for 28 days to obtain an alkali-activated all-solid waste cementitious mortar.

7. The method for preparing an alkali-activated all-solid waste gelled mortar material according to claim 6, characterized in that: In step (a), Al(OH)3 in the low temperature thermally activated aluminum mud is decomposed into γ-Al2O3; the γ-Al2O3 constitutes the Al source for preparing Al-O-Si geopolymer.

8. The method for preparing an alkali-activated all-solid waste gelled mortar material according to claim 7, characterized in that: When the mass fraction of the low-temperature heat-activated aluminum mud in step (c) is 0-40%, the flexural strength of the alkali-activated all-solid waste cementitious mortar material obtained in step (e) is 2.1MP-7.9MP; the compressive strength of the alkali-activated all-solid waste cementitious mortar material is 4.63MPa-67.63MPa.

9. The method for preparing an alkali-activated all-solid waste gelled mortar material according to claim 8, characterized in that: When the mass fraction of the low-temperature thermally activated aluminum mud in step (c) is 10%, the maximum flexural strength of the alkali-activated all-solid waste cementitious mortar material obtained in step (e) is 7.9MPa; the maximum compressive strength of the alkali-activated all-solid waste cementitious mortar material is 67.63MPa.

10. The method for preparing an alkali-activated all-solid waste gelled mortar material according to claim 9, characterized in that: The process of preparing the alkaline activator in step (b) comprises: b1. Prepare water glass and sodium hydroxide in proportion according to the modulus requirements of the alkaline activator; b2. Add water glass and sodium hydroxide gradually into a container according to a certain ratio and stir evenly; b3. Add water to adjust the concentration of the alkali activator according to actual needs; b4. Continue stirring the mixture to ensure uniformity of the base activator; b5. Store the prepared alkaline activator in a sealed container for future use.

Citation Information

Cited By

  • Preparation method of all-solid waste cementing material for roadbed construction

    CN120829257A